Are Oil Industry Mergers Becoming Less Profitable? - Barrows, Samuel D. (International Journal of Energy Economics and Policy, 2018)
Are oil industry mergers becoming less profitable? This study evaluates oil industry consolidations that occur during the sixteen-year time frame between 1998 and 2013 to find out. This quantitative study focuses on the stock price total return performance of acquirer companies over a four year horizon for each merger transaction. The portfolios created from these transactions provide for an analysis of the economics of the mergers after full integration of target companies. Four benchmarks are incorporated to provide various economic adjustment factors. There are seven cases presented that show that oil industry mergers are becoming less profitable. Implications are that companies may chase mergers as an easy way to increase returns, but this may not occur. As ever larger companies chase the remaining players and bid up their selling prices, increased returns may not always be the outcome. Keywords: Oil Industry Mergers, 1998-2013, Brent Crude Oil JEL Classifications: G15, G34, P18